Sensitivity to Immune Checkpoint Blockade in Advanced Non-Small Cell Lung Cancer Patients with EGFR Exon 20 Insertion Mutations - Metro, Giulio (Genes (Basel), 2021)
Besides platinum-based chemotherapy, no established treatment option exists for advanced non-small-cell lung cancer (NSCLC) patients with EGFR exon 20 (Ex20ins) insertion mutations. We sought to determine the clinical outcome of patients with this EGFR mutation subtype in the immunotherapy era. Thirty NSCLCs with EGFR Ex20ins mutations were identified, of whom 15 had received immune checkpoint blockade (ICB) treatment as monotherapy (N = 12), in combination with chemotherapy (N = 2) or with another immunotherapeutic agent (N = 1). The response rate was observed in 1 out of 15 patients (6.7%), median progression-free survival (PFS) was 2.0 months and median overall survival (OS) was 5.3 months. A trend towards an inferior outcome in terms of PFS and OS was observed for patients receiving ICB treatment in the first versus second line setting (PFS: 1.6 months versus 2.7 months, respectively, p = 0.16—OS: 2.0 months versus 8.1 months, respectively, p = 0.09). Median OS from the time of diagnosis of advanced disease was shorter for patients treated with ICB versus those who did not receive immunotherapy (12.9 months versus 25.2 months, respectively, p = 0.08), which difference remained associated with a worse survival outcome at multivariate analysis (p = 0.04). Treatment with ICB is poorly effective in NSCLCs with EGFR Ex20ins mutations, especially when given in the first-line setting. This information is crucial in order to select the optimal treatment strategy for patients with this subtype of EGFR mutation.